Gambaran Tingkat Kompetensi Perawatan Spiritual pada Mahasiswa Program Profesi Ners - Tarisa, Tarisa; Agustina, Hana Rizmadewi; Maulana, Indra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the level of spiritual care competence in Ners Professional Program (PPN) students. The research method used was descriptive quantitative, with data collection techniques using a questionnaire. The results showed that the level of spiritual care competence was 76.6% in the high category and 23.4% in the medium category. In conclusion, almost all respondents have a level of spiritual care competence in the high category, but in the aspects of referring, personal support and client counseling, as well as professionalization and improving the quality of spiritual care, only some respondents have a level of competence in the high category. Keywords: Competence, Ners Professional Program, Spiritual Care